PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN DI DAPUR MAMA IA KOTA BENGKULU - Syavira, Dilla Putri; Ekowati, Sri (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
The purpose of this study is based on the identification of the problems stated above, then the purpose of this study is to determine the quality of service, products to customer satisfaction Dapur Mama IA Bengkulu. The sample of this study amounted to 160 which were determined proportionally. Data collection techniques using questionnaires and data analysis techniques using multiple linear regression. The conclusion of the results of this study is that the Quality of Influence has a positive and significant effect on Customer Satisfaction of Dapur Mama IA Kota Bengkulu, the better the Quality of Service provided the better it will be for the development of Dapur Mama IA Kota Bengkulu. With good Service Quality, it will create Customer Satisfaction by itself. Together, Service Quality and Product Quality have a positive and significant effect on Customer Satisfaction In Dapur Mama IA Kota Bengkulu, the better the Quality of Service provided and the Quality of Products offered will increase Customer Satisfaction. Keywords: Service Quality, Product Quality and Customer Satisfaction